Optimalisasi Lembaga Masyarakat dan Kelompok Disabilitas Desa Wonomerto dalam Peningkatan Nilai Ekonomis “Meronce” melalui Kolaborasi dengan Universitas - Ongkowijoyo, Margareth; Septania, Tamara; Yulianto, Jony Eko (Bakti Budaya: Jurnal Pengabdian kepada masyarakat, 2025)
Wonomerto Village is home to several groups of people with disabilities who face challenges in securing a steady income. However, these groups possess valuable skills in crocheting, knitting, and baking, which they acquired through community empowerment programs facilitated by various universities in the previous year. Recognizing this potential, the 2024 PPK Ormawa program aims to support these individuals by developing a sustainable handicraft business to enhance the community’s economic capacity. From July to October 2024, a dedicated team of university students and lecturers will collaborate with community members to provide comprehensive crochet training, covering everything from production techniques to effective marketing strategies. This program is designed not only to enhance technical skills but also to foster essential soft skills such as teamwork, creativity, and entrepreneurship. By the end of the training, participants will have the opportunity to showcase their crafted goods and apply learned marketing tactics. Initial evaluations indicate that participants are gaining confidence and are better equipped to identify potential business opportunities within the arts and crafts sector. By employing a participatory and community-focused approach, the crochet training initiative is significantly raising awareness and building the capacity of the Wonomerto Village community to leverage its local talents. This initiative not only empowers individuals but also promotes economic growth and sustainability within the village. === Desa Wonomerto memiliki sejumlah kelompok masyarakat penyandang disabilitas yang belum memiliki penghasilan tetap. Namun demikian, kelompok ini memiliki berbagai keterampilan dasar, seperti meronce, merajut, dan membuat kue, yang didapatkan dari beberapa program pemberdayaan masyarakat desa yang dilakukan oleh kampus-kampus lain pada tahun sebelumnya. Sebagai bagian dari program PPK Ormawa 2024, kami menindaklanjuti potensi tersebut dengan berkolaborasi mengembangkan potensi bisnis kerajinan tangan untuk meningkatkan kapasitas ekonomi warga. Selama 4 bulan (Juli—Oktober 2024), tim mahasiswa dan dosen universitas bekerja sama dengan kelompok masyarakat melaksanakan pelatihan meronce, dari latihan produksi hingga pemasaran. Program ini tidak hanya berfokus pada peningkatan keterampilan teknis, tetapi juga pengembangan softskills seperti kerja sama tim, kreativitas, dan kewirausahaan. Di akhir pelatihan ini, para peserta mendemonstrasikan keterampilan mereka dalam memasarkan hasil karya kerajinan. Hasil post-test menunjukkan bahwa warga juga menjadi lebih positif dan mampu mengenali peluang bisnis seni dan kerajinan. Melalui pendekatan partisipatif dan berbasis komunitas, pelatihan meronce berhasil meningkatkan kesadaran dan kapasitas masyarakat Desa Wonomerto dalam memanfaatkan potensi lokal yang dimilikinya.